Atributos de solo e planta e a distribuição de fertilizantes em lavoura cafeeira microterraceada - Pajehú, Levi Fraga (2022)
The use of microterrace between the coffee tree rows in sloping areas has grown in recent years, as it provides the use of small agricultural tractors with hydraulic lifting implements, for more diverse activities that were previously carried out manually or semi-mechanized. However, information on the sustainability of the production system over time is still scarce, and it is important to carry out works that broadly assess: the conditions of physical and chemical degradation of the soil, the temporal behavior of plants, aspects of soil fertility management, and the nutritional status of plants. In this sense, the objective was to evaluate the chemical quality of the soil, the quality of fertilizer distribution, the productivity and the physical quality of the soil under microterrace coffee cultivation. The study was carried out in an arabica coffee crop cultivated in a contour line with microterrace between the lines, 11-year-old red catuaí variety, in the municipality of Ibatiba-ES. An irregular sampling grid was set up, totaling 100 georeferenced points. Soil samples were collected in the projection of the plant crowns, at a depth of 0-0.20m, to assess soil fertility. A mechanized fertilization was carried out in order to evaluate the uniformity of fertilizer distribution. The productivity of the crop was obtained and the width and slope of the micro terraces were measured, in order to evaluate their influence on the uniformity of fertilizer distribution. To evaluate the effect of machine traffic on the soil, the soil penetration resistance, soil density, macroporosity, microporosity and total porosity were determined. The evaluations were carried out in the cultivation lines and in the traffic lines of the pneumatic wheels of the tractors. The data obtained were submitted to classical statistical and geostatistical analyses. High variability in soil chemical attributes was observed, showing regions of low nutrient availability. The fertilizer mass distributed per linear meter was lower than the recommended fixed dose, being affected by the irregular topography of the crop and irregularities on the surface of the microterraces and, mainly, the variations in their width, often less than 2m. The narrow roads and great oscillation in the slope of these “streets” were responsible for the uneven distribution of fertilizers by the tractor-mounted fertilizer machine. Even so, the average productivity of processed coffee was much higher than the national average and that of the state of Espírito Santo, although a high spatial variability of productivity was found in the crop. Regarding the physical analysis of the soil, for almost all the variables measured, there was no statistically significant difference, however there is a tendency to compromise the physical conditions of the soil after the tractor passes, especially under the wheels near the bottom line (at operator left). The results indicate that, due to the slope of the microterrace towards the line below, in the direction of the slope of the terrain, the transfer of weight in the transverse direction of the machine can increase the pressure of the tractor wheels on the left side of the operator.